THE INDONESIAN GOVERNMENT'S INTERVENTION IN MARKET PRICING (CEILING PRICE AND FLOOR PRICE) REVIEWED IN ISLAMIC ECONOMIC PERSPECTIVE - Lusiana, Lusiana; Astrid, Gita (Universitas Islam Negeri Raden Fatah Palembang, 2020)
In a country’s economy, government’s role is undebatable in theories or treasury of economic thought. Through various policies concerning the public sector, the government has a significant role in driving economic growth. One of them is the government’s role in Indonesia. The government’s role in Indonesia in the economic sector is key to a more prosperous society, and it is expected that Indonesia can become a developed and developing country. The economic magnitude and problems such as demand and supply cannot be given up to the market mechanism and free of economic forces. And how the government intervenes in price fixing when a market imbalance exists. Therefore, efforts to balance the growth of various economic sectors to supply must be in line with demand. It needs supervision and regulation by the State or government to obtain balanced economic growth. Thus, the researcher is interested to study government intervention in price fixing in the market and how it is viewed from Islamic economics. The results of this study show that the form of government intervention, both directly and indirectly in price fixing in the market is to protect consumers or producers through a price floor policy. Minimum price fixing or base prices performed by the government aims to protect producers. For instance, the price fixing of grain sold by farmers. And the maximum price fixing policy (price ceiling). The maximum price fixing policy is set to protect consumers. For instance, fix a maximum price for fuel oil, fertilizer, and medicines. In Islamic economics, government intervention is divided into two parts, including interventions that are forbidden or haram, involving government’s involvement in price fixing that are not based on applicable rules or do not consider overall market’s needs. Permitted interventions, including the involvement of the government in price fixing when an emergency occurs, where a third party is required in price fixing to create justice among market participants. Keywords: Government intervention, price fixing, price ceiling and price floor